2021
DOI: 10.26452/ijrps.v12i2.4631
|View full text |Cite
|
Sign up to set email alerts
|

Controlled drug release of levofloxacin from poly (acrylamide) hydrogel

Abstract: Hydrogels are 3D polymer networks capable to absorb and release water or biological fluids. They are stimuli-responsive materials, which can show rapid volume changes with response to small changes in environmental parameters such as ionic strength, pH, and temperature. In this work, we performed a synthesis of Poly(acrylamide) hydrogel and tested for controlled release of levofloxacin hemihydrate as a model drug. We used sodium metabisulfite and potassium persulphate as free radical initiators to prepare hydr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…In the study of Madhusudana et al [41] . poly(acrylamide‐co‐acrylic acid) based hydrogels were synthesized and they found that a higher weight loss was occurred at 384 °C which was attributed to destruction of cross‐linked chain [41] …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In the study of Madhusudana et al [41] . poly(acrylamide‐co‐acrylic acid) based hydrogels were synthesized and they found that a higher weight loss was occurred at 384 °C which was attributed to destruction of cross‐linked chain [41] …”
Section: Resultsmentioning
confidence: 99%
“…[40] In the study of Madhusudana et al [41] poly(acrylamide-coacrylic acid) based hydrogels were synthesized and they found that a higher weight loss was occurred at 384 °C which was attributed to destruction of cross-linked chain. [41] In our study, the weight loss between 150-250 °C can be assigned to MAAc chain degradation and the highest weight loss occurred in the range of 250-450 °C indicating the main decomposition step. The contents of the surfactant and crosslinker did not significantly affect the thermal profile and weight loss (%).…”
Section: Thermal Gravimetric Analysis Of Nanogelsmentioning
confidence: 99%
See 1 more Smart Citation